Between the Material and the Social. Neighborhood Relations of Older People вЂњInsideвЂќ the Infrastructure Deficit - Konstantin A. Galkin (Социологическая наука и социальная практика, 2022)
The article analyzes neighborhood relations in the villages of the Leningrad region. The material was interviews with older people about the peculiarities of rural everyday life and about neighborhood interactions in the context of the infrastructure deficit characteristic of the villages where the study was conducted. Based on the theoretical work of H. Plesner and A. Gelena, the author argues that neighborhood relations can be considered as an important social resource for the older, which is able to adjust and make more comfortable material resources in villages. The adaptability of material and social resources makes it possible to understand the specifics of the meanings of neighborhood relations that are formed in villages, and how aging can be represented based on the key and basic needs of older people. Empirical material was collected in two villages of the Leningrad region. In the landscape caused by the infrastructure deficit, the usual neighborhood solidarity did not work, but such a landscape itself was part of a new solidarity associated with special interactions in which neighborhood relations create the tunability of material resources and are aimed at reciprocal exchange and neighborly assistance and minimizing the problems of infrastructure deficit.